2020
DOI: 10.1002/per.2238
|View full text |Cite
|
Sign up to set email alerts
|

Self–Esteem among Chinese Cohorts: Its Temporal Trend and Its Relationships with Socioecological Factors, 1993–2016

Abstract: Self‐esteem affects individuals in a variety of psychological processes substantially and extensively. While an increase in self‐esteem over time was observed in the USA, different patterns of temporal change in self‐esteem were observed in other societies. We analysed the responses (n = 305 229) collected between 1993 and 2016 from 609 articles to examine the patterns of temporal change in self‐esteem in China and its relations with socioecological conditions. Additionally, we explored the patterns in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Analyses were conducted both weighing and unweighting the sample sizes of individual years (e.g., Clark et al, 2015;Li et al, 2020;Ogihara 2019Ogihara , 2020cOgihara et al 2015;Ogihara & Kusumi 2020;Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses were conducted both weighing and unweighting the sample sizes of individual years (e.g., Clark et al, 2015;Li et al, 2020;Ogihara 2019Ogihara , 2020cOgihara et al 2015;Ogihara & Kusumi 2020;Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This was because the data points were not considered independent, which is necessary to conduct a significance test. Analyses were conducted both weighing and unweighting the sample sizes of individual years (e.g., Clark et al, 2015; Li et al, 2020; Ogihara, 2019; 2020c; Ogihara et al, 2015; Ogihara & Kusumi, 2020; Park et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing 78 countries across 51 years, Santos et al (2017) observed country-level increases in individualist practices (smaller household size, higher percentage of people living alone, and higher divorce rate) and individualist values (higher emphasis on friends relative to family, teaching children to be independent, and higher preference for self-expression). Additionally, studies have documented increases in individualism-related personality constructs, including self-esteem (Gentile et al, 2010;Li et al, 2020;Twenge & Campbell, 2001), self-enhancement (Zhang et al 2017), need for uniqueness (Cai et al, 2018;Ogihara et al, 2015;Twenge et al, 2010), and narcissism (Twenge et al, 2008).…”
Section: Trends In Culture and Personality (Partly Explained By Socio...mentioning
confidence: 99%
“…Such rapid societal change exerts great influence on Chinese culture and psychology (see Cai et al, (2020) for a review), such as narcissism (Gao et al, 2019), need for uniqueness (Cai, Zou, Feng, Liu, & Jing, 2018), and self-esteem (Li, Li, Mei, & Wang, 2020). What should be noted is the change on cultural orientation (Hamamura & Xu, 2015;Ma, Hu, & Gocłowska, 2016;Santos, Varnum, & Grossmann, 2017;Zeng & Greenfield, 2015).…”
Section: The Current Researchmentioning
confidence: 99%